2014
DOI: 10.1002/ccd.25542
|View full text |Cite
|
Sign up to set email alerts
|

One‐year follow‐up of patients treated with new‐generation polymer‐based 38 mm everolimus‐eluting stent: The P38 study

Abstract: The use of a new-generation polymer-based 38 mm EES in a real-world population with unselected long lesions is associated with excellent procedural results and good clinical outcomes at 12-month follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…The strategies adopted for treatment of long diffused lesions in tapered arteries include the use of either multiple stents or a single long stent, both of which are associated with clinical failure due to the potential risk of mechanical mismatch of stent size [1, 4, 5]. Multiple short stents with variable diameters are often implanted (overlapping) to match the size of the long-tapered lesions adequately.…”
Section: Introductionmentioning
confidence: 99%
“…The strategies adopted for treatment of long diffused lesions in tapered arteries include the use of either multiple stents or a single long stent, both of which are associated with clinical failure due to the potential risk of mechanical mismatch of stent size [1, 4, 5]. Multiple short stents with variable diameters are often implanted (overlapping) to match the size of the long-tapered lesions adequately.…”
Section: Introductionmentioning
confidence: 99%
“…These profiles prevented side branch occlusion and periprocedural myocardial injury [17], which may reduce adverse clinical outcomes, even in ultra-long stents [17][18][19]. Second, almost all patients were treated by IVUS guidance, which partially explains the lower restenosis rate in this study compared with previous studies [20]. Moreover, even in the era of DES for complex lesions, it was reported that IVUS-guided PCI was superior to angiographyguided PCI in reducing the risk of MACE [21].…”
Section: Discussionmentioning
confidence: 74%
“…Early reports of second generation DESs in coronary interventions in long lesions raised similar concerns and early results have been conflicting . Sgueglia et al demonstrated a MACE rate of 10.4% and target vessel revascularization rate of 3.9% at one year follow‐up in 203 consecutive patients treated with at least one XIENCE Prime stent in lesions >35 mm . An analysis of 256 patients treated with overlapping everolimus or zotarilumus eluting stents for lesions >34 mm in length was associated with low rates of MACE, TVR, and stent thrombosis at 2‐year follow‐up .…”
Section: Discussionmentioning
confidence: 99%
“…Lesion length remained a predictor of restenosis and repeat revascularization after Drug Eluting Stent (DES) implantation ; however, DES studies were limited by small size, retrospective design or the absence of control groups . With improved design, and better safety and efficacy profile, second generation DES have enabled treatment of longer or multiple overlapping DES in patients with diffuse coronary artery disease . The purpose of this pooled analysis was to evaluate the 1‐year clinical outcome of patients undergoing DES treatment of very long lesions compared to intermediate lesions with the second generation XIENCE everolimus eluting coronary stent systems (EECSS).…”
Section: Introductionmentioning
confidence: 99%